The Role Of Organisational Commitment In Mediating Work-Life Balance On Employee Performance - I Made Dena Julio Mahendra Saputra; Anak Agung Ngurah Oka Suryadinatha Gorda (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
The current study proposed to examine the mediating role of organisational commitment dimensions in the relationship between work-life balance and employee performance at BPR Denpasar City, with assets exceeding 100 billion. With a sample of 249 employees, the research reveals a notable gap in prior studies regarding utilising organisational commitment dimensions as mediators. Questionnaires were used to gather data, which SEM-PLS analysis techniques were then used to process. The findings show that Work-life balance has a positive and significant impact on employee performance, affective commitment, continuance commitment, and normative commitment. Affective, continuance and normative commitment significantly influence employee performance. Affective commitment, continuance commitment, and normative commitment mediate the results of work-life balance and employee performance.